Prototipo de aplicativo WEB para el mejoramiento de registro y control del sistema de información en la IPS Cercap Ltda (2024)
This degree work addresses the deficiencies in the information systems of the IPS CERCAP of Villavicencio and other medical institutions, which suffer from technological obsolescence and resource limitations. To overcome these challenges, a new health management system designed to improve operational efficiency and service quality has been developed and implemented. This system includes functionalities to manage patient crowding, optimize data storage, and improve treatment control and monitoring. Software was implemented based on current web technologies, using Python, HTML5 and SQLite, with remote access capabilities and real-time data synchronization. In addition, advanced security measures such as iterative backups and data encryption were integrated, ensuring the integrity and privacy of the information. This project not only solves existing problems, but also adapts to the dynamics of medical staff and users, promoting continuous improvement in the health system.